Elicitations in the whole classroom events: a comparative study of high vs. low proficient English learners / Golnaz Peyvandi, Sara Choupanzarvijani and Ghazal Monfardkhah - Peyvandi, Golnaz; Choupanzarvijani, Sara; Monfardkhah, Ghazal (Universiti Teknologi MARA, 2023)
There is an argument that teachers’ favoritism toward high-proficient language learners may deprive low-proficient students of learning opportunities and put them at risk of poor learning. This study examines how the modifications that teachers make to Initiation-Response Feedback (IRF) discourse patterns help low- and high-proficient English students have access to opportunities for language learning and how teachers justify their discourse. The participants in this study included three Iranian EFL teachers and their respective English students. Classroom observations stimulated recall interviews, and field notes were used for data collection. The findings showed that they interacted less frequently with the low-proficient English students while they often extended their transactions with the high-proficient English students. Such differences limited the learning opportunities of the less proficient students in the classroom. Modifications were explained under three themes: a) negative self-conceptions of low proficient students; b) quality of interactions with high proficient students; and c) teachers’ concern about job security and their teaching performance. The implications of this study for the Iranian context and other similar EFL contexts are detailed.